Bibliometric Trend Analysis of Household Financial Literacy in Indonesia from 2010 to 2025 - Loso Judijanto (The Eastasouth Journal of Social Science and Humanities, 2026)
Financial literacy in households has emerged as a significant area of research study in recent years, as it has been recognized as a factor that influences financial behavior, inclusion, and socioeconomic welfare. This study proposes to identify the intellectual structure, thematic development, and collaboration trends of research studies on financial literacy in Indonesian households from 2010 to 2025 through a quantitative bibliometric analysis. The data for this study was sourced from the Scopus database and analyzed through the VOSviewer software for co-authorship analysis, citation analysis, keyword co-occurrence analysis, and thematic analysis. The results of this study show that financial literacy is a core theme of research, which is closely linked to household finance, financial education, financial inclusion, and socioeconomic aspects. The co-authorship analysis shows that there is a growing but moderately fragmented collaboration pattern, which is dominated by a few prominent authors, institutions, and countries, especially the United States and prominent international research institutions. Overlay and density analysis clearly shows that there is a significant shift in the themes from conventional financial education and individual financial behavior to more interdisciplinary themes such as digital finance, public health, poverty, and household resilience.